Human Development and Quality of Institutions in Highly Developed Countries - Adam P. Balcerzak; Michal Bernard Pietrzak (Institute of Economic Research (IER), 2015)
The article concentrates on the problem of influence of quality of institutional system in the context of utilizing the potential of knowledge-based economy on the human development in highly developed countries. In order to measure the quality of institutional system a synthetic measure based on multivariate analysis techniques was proposed. To obtain the institutional measure TOPSIS method was applied. To quantify the institutional factors the data from Fraser Institute was used. As diagnostic variables of quality of institutions 29 variables qualified to four aspects of national institutional systems were used: a) formal regulations influencing entrepreneurship; b) effectiveness of juridical system in keeping low level of transaction costs and supporting effectiveness of market mechanism; c) competitive pressure and effectiveness of labour markets; d) financial markets institutions as a stimulator of development of enterprises with high growth potential. Human Development Index proposed within United Nations Development Programme was used for measuring the quality of life. The estimation of relation between institutions and human development was made with econometric dynamic panel model. The estimation was made for 24 European Union countries for the years 2004-2010. The econometric analysis shows the positive influence of quality of institutions on human development in the context of knowledge-based economy in developed countries.
Keywords: I31; O1; C38; 330; institutional economics; quality of institutions; Human Development Index; TOPSIS; panel analysis